Era 5.0 and Local Genius 6.0 Educational Resources for Millennial Educators - Friscilla Sembiring (Jurnal Pendidikan: Media, Strategi, dan Metode, 2026)
Educational resource development in the digital era requires a balanced integration of technological advancement and local cultural identity. Millennial educators need learning resources that are digitally adaptive, human-centered, collaborative, innovative, and culturally grounded. This study aimed to develop educational resources for millennial educators through the integration of Era 5.0 and Local Genius 6.0. The study employed a Research and Development design with product feasibility evaluation, user response analysis, implementation observation, and limited effectiveness analysis. The developed product was a model and guide for educational resources integrating technology-based learning and local wisdom values. The respondents consisted of 50 millennial educators, including students, young teachers, and education practitioners. Expert validation involved material, media, education, local culture, and language experts. Data were collected using validation questionnaires, user response questionnaires, and implementation observation sheets. The results showed that the developed product obtained a very good expert validation score, with an average of 87.20. The highest expert validation score was found in local wisdom and cultural integration, with a score of 90. User responses also showed very good results, with overall satisfaction reaching 82.08. The implementation test showed an average score of 85.80, indicating that the product was highly feasible and practical for educational use. Correlation analysis showed that Era 5.0 Integration had a strong positive relationship with Educational Resource Quality, r = .842, p < .001, while Local Genius 6.0 had a strong positive relationship with Educational Resource Quality, r = .876, p < .001. Educational Resource Quality also had a very strong positive relationship with User Satisfaction, r = .904, p < .001. Regression analysis showed that Era 5.0 Integration contributed 70.9% to Educational Resource Quality, while Local Genius 6.0 contributed 76.7%. The study concludes that educational resources integrating Era 5.0 and Local Genius 6.0 are feasible, practical, culturally relevant, and positively received by millennial educators.